System-targeted management of training in the field of judo - Zekrin, F.Kh.; Zebzeev, V.V.; Zekrin, A.F.; Maltsev, G.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop a concept of system-targeted management of long-term athlete preparation in judo. Methods and structure of the study. The research incorporated systemic, person-centred, activity-based, technological, differentiated, and integrative approaches, providing a comprehensive examination of the sports training process as an integral pedagogical system. Results and conclusions. The provisions of the concept have been substantiated, revealing the essence of long-term judo training as a managed, open, and dynamically developing system oriented towards the achievement of stage-specific target indicators of sporting mastery. An original concept has been formulated, based on the systematic elevation of the level of sporting mastery through the attainment of target benchmarks at each stage of long-term preparation and the technologisation of the training process. It has been established that the effectiveness of preparation is determined by the coherence of pedagogical influences, the individualisation of the training process, consideration of the morphofunctional and typological characteristics of athletes, and the continuity of the stages of sporting improvement. The results obtained may be used in the development of sports training programmes for judoists, the improvement of the selection system, and the management of the training process.